2023
DOI: 10.3389/fpubh.2023.1195660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollution on emergency visits for acute otitis media among children: a case-crossover study in Chongqing, China

Ling Xiao,
Shuping Su,
Cheng Chen
et al.

Abstract: BackgroundMany epidemiological studies have demonstrated the short-term effects of air pollution on acute otitis media (AOM) in children, but few studies have explored the association between AOM and air pollution in Chinese children. This study aimed to analyze the effects of air pollution on emergency visits for AOM among children through a time-stratified case-crossover design in Chongqing, China.MethodsThe outpatient medical records of children from nine main urban districts who presented with AOM between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This suggests that the presence of other pollutants can have a synergistic effect that influences the role of ozone. A case-crossover study analyzing air pollution and acute otitis media in children found that OR became slightly increased after adjusting for ozone ( 22 ). Similarly, Liu et al conducted a national cohort study on air pollution and lung cancer, demonstrating that effect estimates for warm-season ozone were stronger in a multi-pollutant model ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the presence of other pollutants can have a synergistic effect that influences the role of ozone. A case-crossover study analyzing air pollution and acute otitis media in children found that OR became slightly increased after adjusting for ozone ( 22 ). Similarly, Liu et al conducted a national cohort study on air pollution and lung cancer, demonstrating that effect estimates for warm-season ozone were stronger in a multi-pollutant model ( 23 ).…”
Section: Discussionmentioning
confidence: 99%